Role of biotechnology in potato improvement - Tiwari, Jagesh K; Patil, V U; Chaurasia, Kumar N; Sundaresha, S; Kardile, Hemant; Vanishree, G; Dalamu, Dalamu; Bhardwaj, Vinay; Rawat, Shashi; Buckseth, Tanuja; Singh, R K; Chakrabarti, S K (Indian Horticulture, 2020)
Potato is a member of the Solanaceae, a large family with more than 3,000 species. It has one of the richest genetic resources having about 200 wild and primitive species. Potato species range from diploid to hexaploid and are a rich source of genetic resources. The cultivated potato (Solanum tuberosum L., 2n = 4x = 48) is highly amenable to biotechnology. Tremendous advances and refinements in the techniques of plant biotechnology have allowed the problems of crop productivity and quality to be improved in new ways without adverse effects on desired crop traits. A brief summary of successful application of biotechnology in potato improvement is discussed in this article.